Improving the Adsorption Properties of Keratin-Based Goat Hair Toward Reactive Dyes in Dyeing Wastewater by Steam Explosion. Issue 1 (31st December 2023) - Wei, Shijin; Hou, Xiuliang; Liu, Linyun; Tian, Yue; Li, Wei; Xu, Helan
ABSTRACT: Keratin-based goat hair could be used bioadsorbent due to its large availability, biodegradability and low cost. Unfortunately, most available keratin adsorbents are either low in adsorption capacity or high in preparation cost. In this study, goat hair was steam exploded, frozen and disintegrated to prepare the exploded goat hair powder (EGHP), and was further used for the adsorption of reactive blue 19 (RB 19) in dyeing wastewater. Steam explosion significantly increased the adsorption capacity of keratin-based goat hair toward RB 19. Adsorption capacity of RB 19 in EGHP increased from 55 to 427 mg/g after a steam explosion under 1.8 MPa for 150 s. The increased adsorption capacity was mainly due to decreased crystallinity, increased specific surface area from 0.678 to 8.583 m 2 /g and the increased free NH2 groups for EGHP. These structure changes resulted in that more dye molecules could easily and fast entered into the amorphous region of EGHP, thereby improving the adsorption rate and amount of RB 19 dyes. Desorption and regeneration study indicated that the adsorption capacity still maintained 79% after 6 cycles. These results demonstrated that EGHP could be considered as promising bioadsorbent to treat the dyeing wastewater.